Обратная задача для осевого кольцевого канала - Субботович, Валерий Петрович; Темченко, Сергей Александрович (НТУ "ХПИ", 2010)
The new problem-solving procedure of swirl ideal gas axial-symmetric flow inverse problem for the free axial ring duct is described. The procedure specially is developed for use in optimum designing problems of turbomachines flowing pass and take into account features of the optimum alternative organisation and allows essentially paralleling computing processes.
Keywords: устройства турбомашин; двигатели турбореактивные; выхлопные патрубки; системы подвода